PERILAKU MANAJER ATAS ISU MANAJEMEN LINGKUNGAN DILIHAT DARI SEKTOR, REGIONAL, DAN UKURAN PERUSAHAAN - Sari, Novilia Purnama (Business Accounting Review, 2016)
This study aimed to examine the difference of the managerâs attitude onÂ environmental management issue viewed from manufacturing and non manufacturing sector, Regional in Surabaya and non Surabaya (Sidoarjo, Mojokerto, and Gresik), and Firm Size (small and large). This study used quantitative approach, whereas the data obtained through the distribution of questionnaires to manufacturing and non manufacturing firms in Surabaya and around and then processed by using SPSS software. The result showed that there was difference of managerâs attitude onÂ environmental management issue viewed from Sector, Regional, and Firm Size.